The signature of NAO and EA climate patterns on the vertical structure of the canary current upwelling system - Georg, Tina (2023)
The current study aims to analyse the vertical structure of the ocean during upwelling events using in situ and modelled data. Additionally, the influence of climate patterns, namely the North Atlantic Oscillation (NAO) and the East Atlantic (EA) pattern, on the vertical structure and their impact on the upwelling activity are assessed for a period of 25 years (1993-2017). The study focuses on the central part of the Canary Current (25-35 degrees N) with persistent upwelling throughout the year, with an annual cycle and the strongest events from June to September. Upwelling is determined using two different approaches: one index is calculated based on temperature differences between the coastal and the offshore area, and the other is calculated based on wind data and the resulting Ekman transport. Different datasets were chosen according to the indices. Stable coastal upwelling can be observed in the study area for the analysed time span, with differences throughout the latitudes. A deepening of the isothermal layer depth and a cooling of temperatures are observed in the vertical structure of coastal waters, representing a deeper mixing of the ocean and the rise of cooler, denser water towards the surface. During years of a positive NAO, corresponding to a strengthening of the Azores High and the Icelandic Low, stronger winds lead to an intensification of the upwelling activity, an enhanced mixing of the upper ocean, and a deeper (shallower) isothermal layer along the coast (offshore). The opposite is observed in years of negative NAO. Both effects are enhanced in years with a coupled, opposite phase of the EA pattern and are mainly visible during winter months, where the effect of both indices is the greatest. The study therefore suggests that upwelling activities are stronger in winters of positive North Atlantic Oscillation coupled with a negative East Atlantic pattern and emphasizes the importance of interactions between the climate patterns and upwelling.